HIGH SERUM PCBs ARE ASSOCIATED WITH ELEVATION OF SERUM LIPIDS AND CARDIOVASCULAR DISEASE IN A NATIVE AMERICAN POPULATION - Goncharov, Alexey (2007)
We have investigated the relationships among the concentration of total serum polychlorinated biphenyls (PCBs), various PCB congener groupings, and three pesticides to total serum lipids in humans with and without self-reported cardiovascular disease. Blood samples were obtained from 335 adult Akwesasne Mohawks, and were analyzed for 101 PCB congeners, mirex, DDE, and hexachlorobenzene (HCB), as well as serum triglycerides and cholesterol. Structural equation modeling, following the definition of latent variables by means of confirmatory factor analysis, was used to analyze the relationships between serum lipids with PCBs and heart disease. There were significant associations among PCBs, lipids, age, and body mass index (BMI), a fact which justified the application of the structural equation model. Gender of the participant was unrelated to any of the remaining study variables. The results of this study are consistent with a model in which age is considered as both an exogenous explanatory variable and a biological driving mechanism for the acquisition of PCBs. Moreover, the results of this study are consistent with the conclusion that PCBs, acting through P450 enzymes, are directly responsible for increased synthesis of cholesterol and triglycerides, substances known to be major risk factors for cardiovascular disease.